Patterns of Parenting Kebhayangkaraan Character for NCO Education Students - Sandro, Frans; Nurhayati, Sri (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
Non-commissioned officers are part of the Polri members who are the foremost public servants in carrying out their police duties so the success of the Polri is largely determined by the level of competence possessed by each personnel, including aspects of knowledge, skills, and attitudes, especially from elements of leadership in stages in the unity. The method used in this research is the qualitative method. Data collection techniques were carried out by researchers using observation, interviews, and documentation. Based on qualitative research methods, all facts, both written and oral, from primary and secondary data sources are described as they are and then studied to be reduced as concisely as possible to answer the problem. Data analysis techniques in this study include data collection, data reduction, data presentation, and concluding. In carrying out character education, the role of caregivers is vital in developing student character because they have to accompany students every day and are fully responsible for the development of students until they graduate with a minimum score obtained of 65 based on Perkap Number 02 of 2017.